السياحة الصحراوية الخضراء لتحقيق التنمية المحلية المستدامة - غديوي ،يمينة; محسن نزبيدة (جامعة الوادي University of Eloued, 2025)
تهدف هذه الدراسة الى ابراز دور السياحة الصحراوية الخضراء كخيار استراتيجي و فعال للتنمية المحلية المستدامة في الجزائر و كبديل أنسب للثروة الناضبة من خلال توفير مناصب الشغل و جلب العملة الصعبة تعمل أيضا على تنمية و رقي المجتمعات ، و تعتبر ولاية ايليزي خاصة منطقة جانت من أهم المناطق السياحية الصحراوية في الجزائر لتوفرها على مختلف المقومات هذا و محافظتها على البيئة ومن أهم النتائج المتوصل اليها أن السياحة الصحراوية الخضراء تساهم في الحد من استنزاف الموارد الطبيعية و حسن استخدامها أيضا رفع المستوى المعيشي لأصحاب المنطقة و توفير مناصب العمل لهم ، بالاضافة الى تنويع مصادر دخل الاقتصاد الوطني و زيادة الناتج المحلي الخام This study aims to highlight the role of green desert tourism as a strategic and effective option for sustainable local development in Algeria and as a more suitable alternative to depleting wealth by providing jobs and bringing in hard currency. It also works to develop and advance communities, and the state of Illizi is considered one of the most important desert tourist areas in the country. Algeria due to its availability of various components and its preservation of the environment One of the most important results reached is that green desert tourism contributes to reducing the depletion of natural resources and their proper use, as well as raising the standard of living of the region’s owners and providing job positions for them, in addition to diversifying the sources of income of the national economy and increasing the gross domestic product.
Green desert tourism to achieve sustainable local development - Illizi State as a model
مقال
Keywords: سياحة صحراوية خضراء; تنمية محلية مستدامة; جانت; ايليزي; Green desert tourism; Sustainable local development; Janet; Illizi